Penggunaan Minyak Zaitun Ekstra Virgin ke dalam Bahan Pengencer Semen terhadap Kualitas Spermatozoa Ayam Lokal - Khaeruddin, Khaeruddin; Sumantri, C.; Darwati, S.; Arifiantini, R. I. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The aim ofthis study was to examine the preservability of local chicken semen in extender added with various level extra virgin olive oil (EVOO).Semen was collected from three roosters using massage method. Immediately after collection the semen evaluated macro and microscopically. Semen demonstrated   motility, individually divided into five tubes. Each of them diluted with ringer fructose that supplemented with 0%, 4%, 6%, 8% or 10% EVOO. Semen was stored in  refrigerator (5 oC) for sixty hours and evaluated every twelve hours for spermatozoa motility and viability. Results revealed that supplementing the diluent of roosters semen with EVOO and then storing it for different storage periods (, , ,  or  hours) resulted in significant (p .) improvement in spermatooa motility and viabilityin comparison with the control group.Moreover, used of 8% EVOO surpassed other treatments afterin vitro storage for up to 60 hoursand resulted fertilizing ability up to 73.81%.This research conclude that 8% EVOO can be used as antioxidant source for roosters semen during preservation.Keywords : extender, local chicken, extract virgin olive oil, sperma